Endocannabinoid hydrolysis inhibition unmasks that unsaturated fatty acids induce a robust biosynthesis of 2‐arachidonoyl‐glycerol and its congeners in human myeloid leukocytes. Issue 3 (3rd February 2020) - Turcotte, Caroline; Archambault, Anne‐Sophie; Dumais, Élizabeth; Martin, Cyril; Blanchet, Marie‐Renée; Bissonnette, Elyse; Ohashi, Nami; Yamamoto, Keiko; Itoh, Toshimasa; Laviolette, Michel; Veilleux, Alain; Boulet, Louis‐Philippe; et al.
Abstract: The endocannabinoid (eCB) 2‐arachidonoyl‐gycerol (2‐AG) modulates immune responses by activating cannabinoid receptors or through its multiple metabolites, notably eicosanoids. Thus, 2‐AG hydrolysis inhibition might represent an interesting anti‐inflammatory strategy that would simultaneously increase the levels of 2‐AG and decrease those of eicosanoids. Accordingly, 2‐AG hydrolysis inhibition increased 2‐AG half‐life in neutrophils. Under such setting, neutrophils, eosinophils, and monocytes synthesized large amounts of 2‐AG and other monoacylglycerols (MAGs) in response to arachidonic acid (AA) and other unsaturated fatty acids (UFAs). Arachidonic acid and UFAs were ~1000‐fold more potent than G protein‐coupled receptor (GPCR) agonists. Triascin C and thimerosal, which, respectively, inhibit fatty acyl‐CoA synthases and acyl‐CoA transferases, prevented the UFA‐induced MAG biosynthesis, implying glycerolipid remodeling. 2‐AG and other MAG biosynthesis was preceded by that of the corresponding lysophosphatidic acid (LPA). However, we could not directly implicate LPA dephosphorylation in MAG biosynthesis. While GPCR agonists poorly induced 2‐AG biosynthesis, they inhibited that induced by AA by 25%‐50%, suggesting that 2‐AG biosynthesis is decreased when leukocytes are surrounded by a pro‐inflammatory entourage. Our data strongly indicate that human leukocytes use AA and UFAs to biosynthesize biologically significant concentrations of 2‐AG and other MAGs and that hijacking the immune system with 2‐AG hydrolysis inhibitors might diminish inflammation in humans.